2012
DOI: 10.4236/ajps.2012.312216
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genetical Diversity of Some of the Tetraploides Potato Cultivars Grown in Iran

Abstract: The genetical diversity of potato, Solanum tuberosum was assessed using morphological traits. To verify, how this diversity is distributed among the main potato varieties grown in Iran. A total of eleven potato varieties, Ramose, Sante, Shepody, Marfona, Maradona, Milova, Santana, Boren, Cosima, Granola and Agria, were evaluated under vivo and situ experimental conditions in Isfahan, conditions, Iran. Seven phenological, floral and morphological vegetative aerial descriptors, Growth Rate = CGR, Net Assimilatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…It might be interpreted as Granola had the capacity to manufacture higher photosynthates per unit leaf area and Asterix had the lowest capacity for this. The present findings were in agreement with Ranjibar et al (2012) and Esfahai et al (2012), who reported a decreasing pattern of NAR irrespective of potato genotypes. However, the differences of NAR in present findings might be due to genetical difference.…”
Section: Net Assimilation Rate (G M -2 Day -1 )supporting
confidence: 94%
See 2 more Smart Citations
“…It might be interpreted as Granola had the capacity to manufacture higher photosynthates per unit leaf area and Asterix had the lowest capacity for this. The present findings were in agreement with Ranjibar et al (2012) and Esfahai et al (2012), who reported a decreasing pattern of NAR irrespective of potato genotypes. However, the differences of NAR in present findings might be due to genetical difference.…”
Section: Net Assimilation Rate (G M -2 Day -1 )supporting
confidence: 94%
“…From this it may be interpreted that variety Granola had early maturing tendency, but the rest three varieties viz., Asterix, Cardinal and Diamant had late maturing tendency as they maintained higher CGR values till the last stage of sample harvest. Similar results were reported by Mahmud (2012) and Esfahai et al (2012). At later stages, CGR value slowed down because of reduction in absorption of solar radiation and leaf falling (Borrego et al, 2000).…”
Section: Crop Growth Rate (G M -2 Day -1 )supporting
confidence: 82%
See 1 more Smart Citation